2022
DOI: 10.18805/ijare.af-747
|View full text |Cite
|
Sign up to set email alerts
|

The Bio-Insecticidal Activity of Papaya (Carica papaya L.) Leaves Extract against Spodoptera litura Fabr. (Lepidoptera: Noctuidae) Larval Growth

Abstract: Background: Papaya leaves produce several metabolites that may be toxic to an insect pest. In East Java, it is easy to find two cultivars in the yard, plantation, and moors, such as Thailand and local papaya. However, information about their utilization as bio-pesticides remains limited. This study aimed to investigate the relationship between those papaya cultivars and the effect of their extracts on Spodoptera litura larvae. Methods: The Thailand papaya cultivar (TPC) and Indonesian papaya cultivar (IPC) lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It can be seen that the recorded killing rates increase as a result of the interaction between essential oil agent concentration levels and exposure duration levels as they increase. In the same context, his findings indicate (Sofia et al, 2022) indicated the possibility of using papaya leaf extract as a bioinsecticide for Spodoptera litura larvae.…”
Section: Resultsmentioning
confidence: 89%
“…It can be seen that the recorded killing rates increase as a result of the interaction between essential oil agent concentration levels and exposure duration levels as they increase. In the same context, his findings indicate (Sofia et al, 2022) indicated the possibility of using papaya leaf extract as a bioinsecticide for Spodoptera litura larvae.…”
Section: Resultsmentioning
confidence: 89%